Encouraging Creativity as a Mediating Variable in the Relationship between Learning Organizations and Organizational Performance (Case Study: Applied to Magdi Yacoub Foundation for Heart Diseases and Research) - Ahmed , Heba Atef (The Arab Journal of Administration, 2025)
The study aimed to determine the availability of the dimensions of learning organizations at Magdi Yacoub Heart Center in Aswan, to determine the level of furnishing of each of the features of these organizations in supporting the culture of creativity and development of human resources. To determine the impact of the culture of creative thought on improving organizational performance through the development of the performance of the human resource, and finally aimed to take advantage of the concept of an educated organization in improving and developing the performance of human resources working in the organization and thus achieving competitive advantage. To the study, a questionnaire was designed and distributed to a random class of 251 workers, representing 35% of the total, enabling it to accurately represent society, and Cronbach’s alpha test was conducted to measure the sincerity and stability of the study’s questionnaire content. Internal consistency between research variables (as subdivisions), as well as confirmatory factor analysis to test relationships between key axes and their constituent dimensions, and the use of descriptive metrics (arithmetic averages, standard deviation, trend strength, coefficient Difference, rank) to illustrate average values and differing opinions on resolution elements, spearman Correlation analysis to measure the correlation between axes, path analysis to show the direct relationship between the regulatory performance dependent variable and the educated organized independent variable, as well as the indirect relationship via a medium (innovation variable), and finally the one sample T Test average test to measure the effect of the independent variable and the intermediate variable on the child variable. Statistical analysis was carried out using the Ver statistical package. (26.0) - Statistical Package for Social Sciences (SPSS), STATA-Ver.16 statistical programming package to draw path analysis. The results of the study showed that there is a statistically significant impact on all study assignments at the level of indication (0.01) of the educated organization in adopting strategies for organizational change, and the study found that the culture of creativity improves organizational performance, and the culture of dialogue helps to reduce the turnover of employment and activate the role of the organization in its foundation Magdi Yacoub for cardiology and research as an educated organization.